2018
DOI: 10.1177/0013916518773469
|View full text |Cite
|
Sign up to set email alerts
|

Illnesses and Injuries at Nature Preschools

Abstract: Nature preschools, where children spend the entire school day outdoors, are increasingly popular, but their health consequences have not been well researched. This study tested the hypothesis that nature preschools and conventional preschools differ in their illness and injury incidence, by comparing observed illness and injury occurrence in the two types of schools. For 14 weeks, teachers at five nature preschools and four conventional preschools in Seattle, Washington logged absences due to illness. Two natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 55 publications
(103 reference statements)
0
10
0
Order By: Relevance
“…The majority of the studies were conducted in Norway (n=8) (27,(40)(41)(42)(43)(44)(45)(46)(47)(48), USA (n= 7) (49)(50)(51)(52)(53)(54)(55), Australia (n= 6) (56-61) and Canada (n=4) (62)(63)(64)(65). Three studies each were conducted in Finland (66)(67)(68), Germany (69)(70)(71) and Sweden (72)(73)(74).…”
Section: Geographical Locationmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the studies were conducted in Norway (n=8) (27,(40)(41)(42)(43)(44)(45)(46)(47)(48), USA (n= 7) (49)(50)(51)(52)(53)(54)(55), Australia (n= 6) (56-61) and Canada (n=4) (62)(63)(64)(65). Three studies each were conducted in Finland (66)(67)(68), Germany (69)(70)(71) and Sweden (72)(73)(74).…”
Section: Geographical Locationmentioning
confidence: 99%
“…Two studies assessed illnesses and sickness absenteeism using parent or teacher reported days absent from school (43,50). Based on the effect direction plot (Table 4), one study found a non-significant positive association between nature-based ECE and illnesses (i.e.…”
Section: Nature-based Ece (N= 3 Studies N= 2379 Children)mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the differences in the protocols and project structures, positive outcomes have been provided by the authors regarding intrinsic school motivation [18], with positive academic [24,26,27,31], cognitive, and affective outcomes [23]. A decrease in sedentary behaviors and an increase in physical activity levels [21,32,34] have been also been highlighted.…”
Section: Discussionmentioning
confidence: 99%
“…The parent interview and focus group data suggested reduced rates of illness and injury among their children. However, the published studies data found no difference and two studies found a higher incidence of injury within a certain population when comparing naturebased ELC to a traditional ELC setting (Weisshaar et al, 2006;Moen et al, 2007;Söderström et al, 2013;Frenkel et al, 2018). Therefore, this outcome was not applied to the logic model, however, future research should investigate this relationship further.…”
Section: Physical Developmentmentioning
confidence: 96%